AUDIO-VISUAL AIDS MEDIA, LANGUAGE ACQUISITION AND ATTITUDE: AN INITIAL INVESTIGATION IN THE EFL CLASSROOMS - Indrayanti, Iin; Kuntoro, Adi; Romadhon, Syaefani Arif (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Audio-Visual-Aids (AVA) media is a type of media that has long been acknowledged as a teaching aid in foreign language contexts. However, its uses are varied greatly from teacher to teacher depending on the content, inventiveness, classroom needs, and benefits approaches in language learning. Thus, the current research focused on the investigation of the analysis of vocabulary acquisition in the form of nouns and word spellings. In addition, the researcher also determined the influences of the use of the media on learners’ attitudes. A quantitative pre-experimental research approach in a one-group pre-test post-test design was performed involving 35 participants. AVA media was given within four meetings in the form of PowerPoint slides completed with original audio dubbing and fifteen images representing “Things in My Room”. To get further looks at their attitude, the participants also completed a questionnaire responding to 4 Likert Scales regarding their experiences. The analysis was reported to find out the average scores and initial hypotheses using a t-test on two main focuses with a 0.05 significance level. Findings showed a positive significant difference in the average scores of students’ vocabulary acquisition in the pre-test (7.66) and post-test (12.37) or 12.37 7.66. Scores of the tcoun reached higher than the ttable or 18,56438 2,021. Most of the students agreed and strongly agreed, that learning with AVA media brought some benefits to their learning experiences, particularly in the context of Vocabulary Acquisition.